Demographics of Vaccine Hesitancy in Chandigarh, India - Wagner, Abram L.; Shotwell, Abigail R.; Boulton, Matthew L.; Carlson, Bradley F.; Mathew, Joseph L. (Frontiers in Medicine, 2021)
The impact of vaccine hesitancy on childhood immunization in low- and middle-income countries remains largely uncharacterized. This study describes sociodemographic patterns of vaccine hesitancy in Chandigarh, India. Mothers of children <5 years old were sampled from a two-stage cluster, systematic sample based on Anganwadi child care centers in Chandigarh. Vaccine hesitancy was measured using a 10-item Vaccine Hesitancy Scale, which was dichotomized. A multivariable logistic regression assessed the association between socioeconomic factors and vaccine hesitancy score. Among 305 mothers, >97% of mothers thought childhood vaccines were important, effective, and were a good way to protect against disease. However, many preferred their child to receive fewer co-administered vaccines (69%), and were concerned about side effects (39%). Compared to the ‘other caste’ group, scheduled castes or scheduled tribes had 3.48 times greater odds of vaccine hesitancy (95% CI: 1.52, 7.99). Those with a high school education had 0.10 times the odds of vaccine hesitancy compared to those with less education (95% CI: 0.02, 0.61). Finally, those having more antenatal care visits were less vaccine hesitant (≥4 vs <4 visits OR: 0.028, 95% CI: 0.1., 0.76). As India adds more vaccines to its Universal Immunization Program, consideration should be given to education efforts directed at addressing vaccine hesitancy risk factors especially in select sociodemographic groups at higher risk for vaccine hesitancy in order to enhance childhood vaccination coverage.